Full‐thickness skin grafts for surgical defects of the nasal ala – a comprehensive review, approach and outcomes of 186 cases over 9 years. (May 2014) - Tan, E.; Mortimer, N.; Salmon, P.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Various flaps and techniques have been described to reconstruct surgical defects of the ala. Full‐thickness skin grafts have received little attention in the reconstructive literature, particularly for nasal ala defects. What does this study add? Skin grafting for partial‐thickness defects of the nasal ala can yield excellent aesthetic and functional outcomes. In < 50% of cases, dermabrasion was chosen to optimize aesthetic outcomes. The need for dermabrasion was not related to patient, tumour or surgical factors. We provide a comprehensive review and algorithm for repair of nasal ala defects.